Diastolic function assessed with speckle tracking over a decade and its prognostic value: The Copenhagen City Heart Study. Issue 6 (16th May 2021) - Skaarup, Kristoffer Grundtvig; Lassen, Mats Christian Højbjerg; Marott, Jacob Louis; Biering‐Sørensen, Sofie R.; Johansen, Niklas Dyrby; Modin, Daniel; Jørgensen, Peter Godsk; Jensen, Gorm Boje; Schnohr, Peter; Prescott, Eva; Søgaard, Peter; Møgelvang, Rasmus; et al.
Abstract: Background: The ratio of transmitral early filling velocity to early diastolic strain rate (E/e'sr) may be a more accurate measure of LV filling pressure then ratio of early filling pressure to early tissue velocity. The aim of the study was to investigate the impact of age, sex, obesity, smoking, hypertension, hypercholesterolemia, diabetes, physical activity level, socioeconomic, and psychosocial status on E/e'sr over a decade. Additionally, the predictive value of ΔE/e'sr on future major adverse cardiovascular events (MACE) has never been explored. Method: The study included 623 participants from the general population, who participated in the 4th and 5th Copenhagen City Heart Study (CCHS4 and CCHS5). Examinations were median 10 years apart. MACE was the composite endpoint of heart failure, myocardial infarction, and all‐cause death. Results: Follow‐up time was median 5.7 years, and 43 (7%) experienced MACE. Mean age was 51 ± 14 years, and 43% were male. Mean ΔE/e'sr was 2.1 ± 23.0 cm. After multivariable adjustment for demographic, clinical, and biochemistry variables, high age (stand. β‐coef. = .24, P  < .001) and mean arterial blood pressure (MAP) (stand. β‐coef. = .17, P  < .001) were significantly associated with an accelerated increase in E/e'sr In multivariable Cox regression, E/e'sr at CCHS5 and ΔE/e'sr were independent predictors of MACE (HR = 1.20, 95% CI [1.01; 1.42] per 10 cm increase for both). ΔE/e'sr did only provide incremental prognostic value to change in left atrial volume index of the conventional diastolic measurements. Conclusion: In the general population, age and MAP were predictors of an accelerated increase in E/e'sr over a decade. E/e'sr at CCHS5 and ΔE/e'sr were independent predictors of future MACE.